Meningkatkan Kemampuan Menulis Teks Recount sederhana Pada Siswa Kelas VIIIA SMPN 3 Muara Bungo Melalui Penggunaan Metode Example Non Example, Media Pictures, A Puzzle Words Dan A Lotere Boards. - fatmawati fatmawati (Journal Of Language Education and Development (JLed), 2021)
In accordance with the title of classroom action research, the subjects of the research are class VIIIA students of SMP Negeri 3 Muara Bungo in the even semester of the 2018/2019 school year, some of whom have more abilities and others have medium average abilities. The learning process in the first cycle using the Example Non example model, media pictures, a puzzle words and a lottery boards in making recount text has not been able to improve student learning outcomes, because only 56.25% or 18 students succeeded. However, in cycle II it can reach 81.25% or 26 students who are successful and there is an increase to reach 37.5%. Therefore, it can be said that using 2 cycles in this Classroom Action Research (CAR) to improve student learning outcomes, the average value of students with success criteria is > 5.6.